2010
DOI: 10.4269/ajtmh.2010.10-0173
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Raccoons (Procyon lotor) with West Nile Virus

Abstract: Abstract. To characterize the responses of raccoons to West Nile virus (WNV) infection, we subcutaneously exposed them to WNV. Moderately high viremia titers (≤ 10 4.6 plaque forming units [PFU]/mL of serum) were noted in select individuals; however, peak viremia titers were variable and viremia was detectable in some individuals as late as 10 days post-inoculation (DPI). In addition, fecal shedding was prolonged in some animals (e.g., between 6 and 13 DPI in one individual), with up to10 5.0 PFU/fecal swab de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Among these three species, only raccoons have been evaluated experimentally for amplifying host status; peak viremia titers below the threshold of infection for Culex pipiens suggest raccoons play a limited role in virus transmission. 48 West Nile virus-positive mosquito pools and human cases were reported within Ontario in 2015 and 2016, 46 during which time these seropositive mammals were likely infected based on their age and average life expectancy. 40,41 These data are consistent with prior serosurveys in other regions, such as Colorado, where multiple mammalian species, including fox squirrels (Sciurus niger), raccoons, striped skunks, and Virginia opossums, were seropositive for WNV.…”
Section: Discussionmentioning
confidence: 99%
“…Among these three species, only raccoons have been evaluated experimentally for amplifying host status; peak viremia titers below the threshold of infection for Culex pipiens suggest raccoons play a limited role in virus transmission. 48 West Nile virus-positive mosquito pools and human cases were reported within Ontario in 2015 and 2016, 46 during which time these seropositive mammals were likely infected based on their age and average life expectancy. 40,41 These data are consistent with prior serosurveys in other regions, such as Colorado, where multiple mammalian species, including fox squirrels (Sciurus niger), raccoons, striped skunks, and Virginia opossums, were seropositive for WNV.…”
Section: Discussionmentioning
confidence: 99%
“…Raccoons ( Procyon lotor ) were thought to be potential reservoirs and amplifiers of WNV in Europe but that hypothesis is still surrounded by controversies and requires more studies [ 230 , 231 ]. Seroprevalences studies of WNV in raccoons in the USA have reported WNV seroprevalence ranging between 34–54% [ 230 , 232 , 233 ].…”
Section: Wnv Ecologymentioning
confidence: 99%
“…Although small mammals can become infected with WNV and outbreaks in humans and horses regularly occur, mammalian infection is not thought to substantially contribute to viral maintenance in nature. [3][4][5][6][7] The envelope (E) protein of most flaviviruses contains an N-linked glycosylation site at amino acids 153/154; DENV contains a second site at E protein amino acid 67. Glycosylation of the E protein is not required for virion formation or infectivity because naturally non-glycosylated isolates of St. Louis encephalitis virus, yellow fever virus, and WNV have been identified.…”
Section: Introductionmentioning
confidence: 99%